2017
DOI: 10.1016/j.psychres.2017.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences among medically serious suicide attempters aged 15–54 years in rural China

Abstract: China is one of few countries which reported higher female suicide rates in the worldwide. However, little is known about the gender differences among Chinese rural suicide attempters. This study aims to analyze the gender differences among medically serious suicide attempters aged 15–54 years in rural China. Subjects were 791 medically serious suicide attempters and 791 controls aged 15–54 years in rural China. Socio-demographic, psychological and some critical variables were assessed in the interview. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…In this review, we also observed a suggested lower prevalence of psychiatric disorders in studies that included fewer males than females. There were very few studies that reported on sex specific prevalence rates, and whilst some supported our findings of a higher rate in males [121,135], others did not [91,102,117,121,135,148,151,160].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In this review, we also observed a suggested lower prevalence of psychiatric disorders in studies that included fewer males than females. There were very few studies that reported on sex specific prevalence rates, and whilst some supported our findings of a higher rate in males [121,135], others did not [91,102,117,121,135,148,151,160].…”
Section: Discussionsupporting
confidence: 76%
“…There were, however, only 8 studies that presented sex stratified prevalence of psychiatric morbidity from India, China, and Iran [91,102,117,121,135,148,151,160]. Two studies reported a higher prevalence of psychiatric morbidity in males than females [121,135], one reported a higher prevalence in females [117], and the remaining 5 studies reported no differences [91,102,148,151,160]. Studies that used a clinician’s diagnosis of psychiatric morbidity reported a higher prevalence of anxiety related disorders (15%, 95% CI 11%–19%) than those that used a validated diagnostic interview (8%, 95% CI 7%–10%).…”
Section: Resultsmentioning
confidence: 99%
“…Although suicide brings more death to males, females register many more unsuccessful attempts (Sava and Papari, 2015), which is consistent with our finding. Compared with males, female suicide attempters are more likely to be influenced by social and interpersonal factors (Sun and Zhang, 2017), which is a key issue for people with schizotypal traits. Nonetheless, the negative relationship between schizotypy and meaningfulness has to date received relatively little attention.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we also analyzed the social-demographic and work-related variables, and the results found that female, doctor degree, physical diseases are associated with a higher prevalence of lifetime and one-year suicidal ideation. The previous studies have proofed the higher prevalence of suicidal behavior among Chinese females in different populations [59,60]. The association between physical diseases also has been identified in many studies worldwide [61].…”
Section: Discussionmentioning
confidence: 77%